Victorian writing about risk : imagining a safe England in a dangerous world - Freedgood, Elaine (Cambridge ; New York : Cambridge University Press, 2000)
"In Victorian Writing about Risk, Elaine Freedgood explores the geography of risk produced by a wide spectrum of once-popular literature, including works on politic economy, sanitary reform, balloon flight, Alpine mountaineering and African exploration. The consolations offered by this geography of risk are precariously predicated on the stability of dominant Victorian definitions of people and places. Women, men, the laboring and middle classes, the English and the Irish, Africa and Africans: all have assigned identities that allow risk to be located and contained. When identities shift and boundaries fail, danger and safety begin to appear in all the wrong places. The texts that this study focuses on reveal the ways in which risk moralizes and naturalizes the economic and political institutions of industrial, imperial culture during a period of unprecedented expansion and change."--Jacket
Introduction: the practice of paradise -- 1. Banishing panic: J.R. McCulloch, Harriet Martineau and the popularization of political economy -- 2. The rhetoric of visible hands: Edwin Chadwick, Florence Nightingale and the popularization of sanitary reform -- 3. Groundless optimism: regression in the service of the ego, England and empire in Victorian ballooning memoirs -- 4. The uses of pain: cultural masochism and the colonization of the future in Victorian mountaineering memoirs -- 5. A field for enterprise: the memoirs of David Livingstone and Mary Kingsley.
Includes bibliographical references (pages 199-211) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Travelers' writings, English -- History and criticism; English prose literature -- 19th century -- History and criticism; Risk perception -- Great Britain -- History -- 19th century; British -- Foreign countries -- History -- 19th century; Great Britain -- Foreign relations -- 1837-1901.; Travel writing -- History -- 19th century; Travel in literature; Risk in literature; Autobiography; Autobiographies as Topic; Écrits de voyageurs anglais -- Histoire et critique; Prose anglaise -- 19e siècle -- Histoire et critique; Perception du risque -- Grande-Bretagne -- Histoire -- 19e siècle.; Britanniques -- Pays étrangers -- Histoire -- 19e siècle.; Grande-Bretagne -- Relations extérieures -- 1837-1901.; Voyage -- Art d'écrire -- Histoire -- 19e siècle.; Voyage dans la littérature.; Risque dans la littérature.; Autobiographie; autobiography (genre); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Autobiography; British -- Foreign countries; Diplomatic relations; English prose literature; Risk in literature; Risk perception; Travel in literature; Travel writing; Travelers' writings, English; Great Britain; Reiseliteratur; Abenteuerliteratur; Risico nemen; Victoriaanse tijd; Veiligheid; Reisverhalen; Englisch; 1800-1901; Criticism, interpretation, etc; History